Strategi Ekspansi Penyaluran Kredit UKM (Studi Kasus PT Bank BJB tbk) - Hidayat, Ayat; Koesrindartoto, Deddy P. (The Indonesian Journal of Business Administration, 2013)
Data of Bank Indonesia stated that Small Medium Enterprises (SME) loan portfolio by the end of April 2012 amounted to 20.65% of the total national banking loans. Currently the banks, ranging from the state owned banks, private banks, rural banks (BPR), joint venture banks, to foreign banks are competing to grab SME market. The reason is that the SME sector is a profitable and huge market. Bank BJB is one of the commercial banks based in West Java, where in the region, small medium enterprises are growing. It is opportunity of Bank BJB to focus on expanding its SME loans to the region. Existing strategies that adopted by Bank BJB is by opening new branch offices, channeling strategy and acquiring of existing BPR. This study aims to compare the three strategies above in terms of strength, weakness, opportunity and threat that likely occur. Method of analysis to be used is SWOT analysis. Once known Strength, Weakness, Opportunity and Threat for each strategy, then use the TOWS matrix to map out the existing strategy that fits with the use of strength, weakness, opportunity and threat for SME lending expansion of Bank BJB. CAMELS ratio will be used to measure the performance of BPR while Discounted Cash Flow (DCF) is method to valuate the value of BPR. Based on the results, it can be seen that strategy of opening a new branch has strength in terms of management authority which head office can control loans quality of the branch office while the weakness is difficult to find a strategic location for new branch office and it needs big initial investment. Strategy of opening new branches will remain to continue, especially in the district and sub-district area. The channeling strategy has advantage because it does not need big initial investment so the capital can be disbursed as loans effectively. This strategy will be implemented primarily to BPR bank that has broad coverage and low of NPL. The acquisition strategy has advantages in terms of fully authority of head office to control loans quality of the branch offices. This strategy can expand its loans by the existing infrastructure and resources of BPR acquired.Â Keywords: SME lending, acquisition, expansion strategy